(untitled) (Research, Society and Development, 2022)
Objective: To analyze the main complications in cataract surgery and how recovery occurs in the postoperative period, with an emphasis on vision loss. Methodology: This research is an integrative literature review. Databases of scientific articles were used to perform the searches: US National Library of Medicine (PubMed) and Scientific Electronic Library Online (SciELO) Latin American and Caribbean Literature in Health Sciences (LILACS) and Virtual Health Library (BVS) of scientific data until May 15, 2022, without language restriction, with studies published in the last 10 years between 2012 and 2022. The keywords “cataract” AND “complications” were used. Result and Discussion: Cataract has the potential to cause several complications that may be due to disease or surgery itself, and may occur during the performance of the surgical procedure or after. Complications include subtypes of glaucoma, infection such as panophthalmitis inflammation, lens subluxation and double vision (diplopia). Conclusion: Although the surgery presents a large number of complications and signs, their incidence and severity are very low, thus making it one of the safest surgeries in the world.